Timing of Complete Revascularization in Patients with STEMI and Multivessel Disease: A Systematic Review and Meta-Analysis - Giuseppe Panuccio; Nadia Salerno; Salvatore De Rosa; Daniele Torella (Reviews in Cardiovascular Medicine, 2023)
Background: About half of patients with ST-segment Elevation Myocardial Infarction (STEMI) have multivessel coronary artery disease (MVD). Our aim was to provide a quantitative comparison of single-stage complete revascularization during the index revascularization versus deferred staged complete revascularization in STEMI patients with MVD. Methods: All studies evaluating patients with STEMI and MVD were included. The primary endpoint was a composite of all-cause death, myocardial infarction and repeat revascularization. Secondary endpoints were cardiovascular death, acute kidney injury and trial defined major bleeding. Results: Eight studies and 2256 patients with STEMI and MVD were included. No difference was evident in the rate of the primary composite endpoint among the study group (Risk Ratio 0.95; 95% CI 0.71–1.27, p = 0.74), while meta-regression showed a significant interaction with drug eluting stent (DES) use (Coefficient –0.005; 95% CI –0.01 to –0.001; p = 0.007). Higher rates of cardiovascular (CV) death were found in the immediate complete revascularization group (5.0% vs 2.6%; Risk Ratio 0.39; 95% CI 0.25–0.62; p < 0.01). Conclusions: Our analysis documented similar clinical outcomes with either single-stage immediate complete revascularization and delayed staged complete revascularization. Secondary analyses suggest that an increase in cardiovascular death might be expected with single-stage percutaneous coronary intervention (PCI). While new randomized trials on the topic are ongoing, revascularization can be personalized and guided by the acute clinical setting, patients’-related factors and workflow logistics.